Zmiany w poziomie rozwoju i życia w układzie przestrzennym i regionalnym Polski w warunkach transformacji - Kociszewski, Jerzy (The Changes of the Level of the Development and Life Level in the Spatial and Regional System During the Transformation Period in Poland, 2005)
The study analyzes the of the as transformation for the development and life level in the spatial and regional system in Poland. The realized effectiveness model according to the economic growth paradigm, in relation to the period of Polish People's Republic causes the differentiation and intensification of the divergence between them. Its result is the growth of superiority in the development and life level in relation to the national pattern, in the central regions, mainly under the influence of the Warsaw agglomeration, systematically lowering in the western and northern regions as well as constantly very low level in the eastern regions. Among 16 Polish regions only in the Mazowiecki region the increasing development level accompanies life level, differently than in the case of most of them, in which it stays at the same level, and as regards the life level it falls. The difference between the regions with the higher and the lowest development level has increased.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 153-169